When silence is golden: The use of strategic silence in crisis management - LE, Phuong D. (Institutional Knowledge at Singapore Management University, 2019)
Purpose: Scholars have discouraged using silence in crises as it magnifies the information vacuum (see Pang, 2013). The purpose of this paper is to argue for its viability and explore the type of silence that can be used. Design/methodology/approach: Eight international cases were analyzed to examine how silence was adopted, sustained and broken. Findings: The findings uncovered three intention-based typologies of strategic silence: delaying, avoiding and hiding silences. Among such, avoiding/hiding silence intensified crises and adversely affected post-silence organizational image when forcefully broken, while delaying silence helped preserve/restore image with primary stakeholders if successfully sustained and broken as planned. Research limitations/implications: First, these findings may lack generalizability due to the limited number of cases studied. Second, local sentiments may not be fully represented in the English-language news examined as they may be written for a different audience. Finally, a number of cases studied were still ongoing at the time of writing, so the overall effectiveness of the strategy employed might be compromised as future events unfold. Practical implications: A stage-based practical guide to adopting delaying silence is proposed as a supporting strategy before the execution of crisis response strategies. Originality/value: This is one of the few studies to examine the role of silence in crisis communication as silence is not recognized as a type of response in dominant crisis theories – be it the situational crisis communication theory or the image repair theory (An and Cheng, 2010; Benoit, 2015; Benoit and Pang, 2008; Xu and Li, 2013).